(untitled) (Research, Society and Development, 2020)
The problematic street situation has always existed in Brazil, since the time of colonization, and corresponds to a population group with some characteristics in common, such as extreme poverty and homelessness, being seen in a problematic way for the Brazilian State. This article aims to analyze the situation of the homeless population, based on Public Policies and to identify improvements in prevention and health care. To this end, an integrative literature review was carried out, with a qualitative approach carried out through the VHL database, where the inclusion criteria were: articles in Portuguese and English, indexed in full, available for reading and with a time frame of 6 years (2015 -2020). Exclusion criteria were used, with articles that were repeated or that did not apply the proposed theme being discarded. After applying the criteria, 13 articles were selected to compose the study. In this way, it was possible to analyze that the studies that address the theme of the homeless population in a more comprehensive way, with a main focus on their social determinants. There is an urgent need to raise discussions about vulnerabilities and prejudice towards this population, going far beyond the discussion about Public Policies. Thus, it was observed the existence of a parallel and inhuman reality, surrounded by prejudices and stigmas, and it is important that health professionals build actions to reverse or mitigate the processes of social exclusion, knowing their peculiarities, focusing on prevention and prevention practices. attention to the health of this population.